2022
DOI: 10.1002/anie.202215360
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein as a Target for Metallo‐Anti‐Neurodegenerative Agents

Abstract: The unique thermodynamic and kinetic coordination chemistry of ruthenium allows it to modulate key adverse aggregation and membrane interactions of α‐synuclein (α‐syn) associated with Parkinson's disease. We show that the low‐toxic RuIII complex trans‐[ImH][RuCl4(Me2SO)(Im)] (NAMI‐A) has dual inhibitory effects on both aggregation and membrane interactions of α‐syn with submicromolar affinity, and disassembles pre‐formed fibrils. NAMI‐A abolishes the cytotoxicity of α‐syn towards neuronal cells and mitigates n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Similarly, heterodinuclear complexes containing both Pt­(II) and Ru­(II) metal ions bridged by 2,3-bis­(2-pyridyl)­benzoquinoxaline ligands exhibit a different mechanism of action where the inhibition of Aβ aggregation is due to Aβ 1–42 conformational variations that force it to remain in the monomeric form . Very recently, it has been shown that NAMI-A has a dual inhibitory effect on both aggregation and membrane interaction of α-synuclein (α-syn) associated with Parkinson’s disease (PD) . This complex abolishes the cytotoxicity of α-syn toward neuronal cells and mitigates neurodegeneration and motor impairments in a rat model of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, heterodinuclear complexes containing both Pt­(II) and Ru­(II) metal ions bridged by 2,3-bis­(2-pyridyl)­benzoquinoxaline ligands exhibit a different mechanism of action where the inhibition of Aβ aggregation is due to Aβ 1–42 conformational variations that force it to remain in the monomeric form . Very recently, it has been shown that NAMI-A has a dual inhibitory effect on both aggregation and membrane interaction of α-synuclein (α-syn) associated with Parkinson’s disease (PD) . This complex abolishes the cytotoxicity of α-syn toward neuronal cells and mitigates neurodegeneration and motor impairments in a rat model of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Protein misfolding is a process in which protein fails to fold into its native functional conformation and will lead to protein aggregates in cells . A growing number of studies have demonstrated that the abnormal aggregation of proteins is associated with many common neurogenerative diseases, , such as Alzheimer’s disease, , Parkinson’s disease, , and Huntington’s disease . Canonically, protein aggregation is closely related to organelles such as mitochondria and lysosome .…”
Section: Introductionmentioning
confidence: 99%
“…The IDP of this article’s interest, alpha-synuclein ( α S) has remained an important drug-target 2427 owing to its long-rooted association with neurodegenerative diseases. Often, the early aggregation stages of α S into small oligomers is implicated in the causation of Parkinson’s disease 2831 and a potential therapeutic strategy has been the stabilization of α S in soluble monomeric form.…”
Section: Introductionmentioning
confidence: 99%